NUTRITIONAL STATUS OF OLDER ADULTS ACCORDING TO DATA FROM THE FOOD AND NUTRITION SURVEILLANCE SYSTEM (SISVAN) IN THE MUNICIPALITY OF TERESINA/PI (REMUNOM, 2026)
This study aimed to analyze the nutritional status of older adults in Teresina, PI, Brazil, from 2020 to 2024, using data from the Food and Nutrition Surveillance System (SISVAN). This is a descriptive, quantitative, and documentary study based on secondary data obtained from Primary Health Care. Records of individuals aged 60 years or older registered in SISVAN were evaluated and classified according to body mass index (BMI) into underweight, normal weight, and overweight. The results indicated a high prevalence of overweight, especially among women, as well as a trend toward stability in the rates of normal weight and underweight over the years analyzed. It was also observed that factors such as population aging, changes in dietary patterns, and the impact of the COVID-19 pandemic may have contributed to the persistence of a concerning nutritional profile. These findings highlight the importance of continuous monitoring of the nutritional status of older adults and the need for public policies aimed at promoting healthy eating, preventing obesity, and maintaining adequate body weight. Thus, systematic monitoring through SISVAN is essential to support intersectoral actions that promote active and healthy aging.